The clinical value of measuring antiphospholipid antibodies in high risk primigravidae and nullipara, a case control study - Mansy, Amr A.; Al-Gizawi, Nermeen N.; Gaballah, AbdEl-Latif; El-Sawi, Noha AbdEl; AL-Gendi, Wessam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Antiphospholipid syndrome (APS) is an autoimmune thrombophilic condition that is marked by the presence in blood of antibodies that recognize and attack phospholipid-binding proteins, rather than phospholipid itself. The clinical manifestations of APS include vascular thrombosis and pregnancy complications, especially recurrent spontaneous miscarriages and, less frequently maternal thrombosis. Obstetric manifestations of APS are not restricted to fetal loss. Current APS criteria include preterm labour, oligohydramnios, neonatal complications as prematurity-estimated at 30-60% and more common in SLE patients, intrauterine growth restriction “IUGR”, fetal distress and rarely fetal or neonatal thrombosis, associated maternal obstetric complications as pre-eclampsia/eclampsia and HELLP syndrome, arterial or venous thrombosis and other aPL-related complications as placental insufficiency. Methods: The study included 90 primigravida and nullipara during their first trimester antenatal care visits, divided into 2 groups after signing a well-informed consent to declare their willing to participate in the study. All selected cases and control group were subjected to demographic data, thorough history taking, clinical examination focused on arterial blood pressure, body mass index, laboratory investigations fasting and random blood glucose level, serum analysis of anti-phospholipid anti bodies by enzyme linked immunosorbent assay (ELISA) including anticardiolipin antibodies (ACL), anti β2-glycoprotein I antibodies (Anti β2 GPI) and citrated sample for lupus anticoagulant test (LA). Results: We can conclude from the current study that aPLs namely lupus anticoagulant is significantly more common in high risk primigravidae having obesity, hypertension and diabetes mellitus than those without risk factors. Conclusions: aPLs antibodies as lupus anticoagulant is significantly more common in high risk primigravidae having obesity, hypertension and diabetes mellitus than those without risk factors.